2021
DOI: 10.7759/cureus.15660
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous Cholecystitis Secondary to Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum may be implicated in cases of emphysematous cholecystitis (EC) and carries a high mortality risk, especially in individuals with heart disease, renal insufficiency, and underlying malignancy. Fusobacterium infections are rarely detected in the setting of cholecystitis possibly due to the difficulty with properly culturing the bacteria. We describe a case of a patient with EC in whom blood cultures were positive for growth of F. nucleatum in one of two samples. The patient was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Prevotella was found to be the most abundant anaerobic organism isolated from patients undergoing liver resection who developed infected post-operative bilomas [28].Therefore, it is suggested that Prevotella may be an important role in biliary sepsis with implications for targeting it for treatment. Fusobacterium is an uncommon infectious organism, however, when present is associated with significant mortality rates [29,30]. It has been demonstrated to be an important causative organism of biliary sepsis (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevotella was found to be the most abundant anaerobic organism isolated from patients undergoing liver resection who developed infected post-operative bilomas [28].Therefore, it is suggested that Prevotella may be an important role in biliary sepsis with implications for targeting it for treatment. Fusobacterium is an uncommon infectious organism, however, when present is associated with significant mortality rates [29,30]. It has been demonstrated to be an important causative organism of biliary sepsis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangitis requires an urgent procedure such as endoscopic retrograde pancreaticoduodenoscopy (ERCP) to allow drainage of the biliary system. This drainage allows the restoration of normal bile flow which allows the resolution of this disorder [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that Prevotella may be an important role in biliary sepsis with implications for targeting it for treatment. Fusobacterium is an uncommon infectious organism; however, when present, it is associated with significant mortality rates [ 30 , 31 ]. It has been demonstrated to be an important causative organism of biliary sepsis (e.g., in emphysematous cholecystitis) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon was encountered during an autopsy and the condition was described as presence of gas in the lumen of gall bladder or biliary tree [3]. The reason behind the presence of air is bile infected with gas-producing bacteria (Clostridium species, Fusobacterium nucleatum, Escherichia coli, Klebsiella species, and anaerobic streptococci) [4,5]. According to the reports, the ischemia of the gall bladder is the main contributing factor for secondary infection occurrence with gas producing bacteria [6].…”
Section: Discussionmentioning
confidence: 99%